2016
DOI: 10.4300/jgme-d-15-00240.1
|View full text |Cite
|
Sign up to set email alerts
|

Racing Against the Clock: Internal Medicine Residents' Time Spent On Electronic Health Records

Abstract: Background Since the late 1980s, resident physicians have spent increasing amounts of time on electronic health record (EHR) data entry and retrieval. Objective longitudinal data measuring time spent on the EHR are lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 22 publications
3
50
1
Order By: Relevance
“…Another time-motion study found medical interns spent 12% of time with patients, 15% in educational activities, and 40% in computer use. 10 These findings are consistent with other reports of patient care versus documentation in the current era, [11][12][13][14] which is in contrast to earlier studies showing more time spent in patient care. 15 In line with evidence that deep learning requires meaningful interactions, residents report that they learn best from attendings and from clinical work, which drives their reading.…”
Section: Decreased Time With Patients and Attendingscontrasting
confidence: 55%
See 1 more Smart Citation
“…Another time-motion study found medical interns spent 12% of time with patients, 15% in educational activities, and 40% in computer use. 10 These findings are consistent with other reports of patient care versus documentation in the current era, [11][12][13][14] which is in contrast to earlier studies showing more time spent in patient care. 15 In line with evidence that deep learning requires meaningful interactions, residents report that they learn best from attendings and from clinical work, which drives their reading.…”
Section: Decreased Time With Patients and Attendingscontrasting
confidence: 55%
“…18,19 The electronic health record (EHR) has squeezed resident time even further. 14,20,21 Resident perceptions may not be the best method to determine optimal learning methods, but their perceptions are reality when assessing satisfaction with training and later practice. Collegial relations with attendings were a key factor in resident satisfaction in a national survey of 248 surgical residencies.…”
Section: Decreased Time With Patients and Attendingsmentioning
confidence: 99%
“…Medical students spend a significant amount of time using the EHR during their clerkship experiences and will continue to do so as they progress to residency. 1,2 However, formal training varies between institutions and leaves gaps in data-gathering skills, 3 documentation skills, 4 and order entry. 5 We designed a workshop using a simulated EHR to teach these skills.…”
Section: Introductionmentioning
confidence: 99%
“…The article by Chen et al 4 in this issue of the Journal of Graduate Medical Education reports the findings of a study that used the log data generated by firstyear internal medicine residents' mouse clicks and keystrokes using the institutional EHR. The research showed that the average time spent on the system was approximately 7 hours per day in July, which fell to 5 hours per day by January.…”
mentioning
confidence: 99%
“…Tracking and monitoring are key aspects of Internet technologies, 6 and Chen et al have illustrated this power by using the logs of individual residents' clicks and keystrokes to make inferences about their behaviors and the value of those behaviors. 4 It should be noted that Chen et al are not the only researchers to use log data to make inferences about clinical behaviors; 7 there seems to be a growing acceptance of this approach. Most clinical activities are ephemeral (unless captured on video), and their value depends on whether and how they were observed, as well as on their outcomes.…”
mentioning
confidence: 99%